(untitled) (Journal of Hama University, 2026)
The rhythmic system, with its various types, played a prominent role in determining the poetic features of the poem by the poet Mustafa Al-Hadri; not only because it is a system that goes beyond the famous music of Al-Khalil, but also because that system revealed many of the aesthetic-psychological connotations that surround Al-Hadri’s poetry, especially since the rhythmic texture was clearly related to other artistic elements, such as the composite image, antithetical pairs, paradox, deviation, and choice. In addition to all of this, this style has illuminated many aspects of the clash between the poet and the surrounding reality, which is full of corruption and evil. Then, the emotional deprivation was not far from the internal musical formations that showed the recipient the great rift between the poet and the woman in an unrelated direction.